Pengaruh Media Sosial, Kreativitas dan Motivasi Kewirausahaan terhadap Keberhasilan Usaha pada UMKM Food & Beverage di Jember - Maya Sabrina, Adelia Annissa; Fatimah, Feti; Rahayu, Jekti (Lembaga Pengembangan Kinerja Dosen, 2025)
Business success is the primary goal that every company strives to achieve, with all activities focused on reaching it. In general, success reflects a condition that is better than before. MSMEs (Micro, Small, and Medium Enterprises) play a crucial role in supporting national economic growth, particularly through meeting the needs of local communities. This study aims to analyze the influence of Social Media, Creativity, and Entrepreneurial Motivation on the business success of coffee shop entrepreneurs in the Jember area. The research employs a descriptive quantitative approach with a saturated sampling method, involving 100 respondents who are MSME actors in the food and beverage sector, specifically coffee shops. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, multiple linear regression, as well as t-test and F-test. The results indicate that all three independent variables have a positive and significant effect on business success, both partially and simultaneously. Based on these findings, it is recommended that MSME actors actively utilize social media as a promotional tool and continue to enhance their creativity and entrepreneurial motivation through training to improve managerial and marketing capabilities.